Design Improvement of Manual Rigid Frame Wheelchair Based On Ergonomic Factors - Tan, Ying Wei; Mustafa El Bakri, Helmy (Progress in Engineering Application and Technology, 2022)
This research focused on the redesign of manual rigid frame wheelchair based on ergonomics factors. Ergonomics is a research science that studies the relationships between humans and other system components and a profession that uses theory and design techniques to improve human well-being and overall system efficiency. Meanwhile, the wheelchair is an assistive device most commonly used by disabled persons for daily activities and mobility. To ensure the comfortability of the wheelchair and eliminate the risk of injuries, the wheelchair designs must typically accommodate a wide range of people ergonomically. The main objectives of this project were to propose an ergonomic manual rigid frame wheelchair and to examine the strength of the redesign manual rigid wheelchair by undergoing static study. Furthermore, the selection of material for the wheelchair also will be made to fulfil a sustainable and durable in the proposed design. Rapid Entire Body Assessment (REBA) was chosen as an ergonomic assessment tool to indicate the risk of musculoskeletal disorders (MSD) by analyzing it through Kinovea software. The REBA score of current manual rigid frame wheelchair design was 8 which indicated that this design was causing high level of MSD risk that further investigation and changes needed. Meanwhile, SOLIDWORKS software was used to propose the redesign and conducted the static simulation. The features like height-adjustable headrest, armrest and attachable leg rests were added to the proposed design. After inserting an ergonomic manikin into the proposed design through CATIA software, the REBA score implemented was 2 which indicated a low level of MSD risk. The REBA score was reduced by 75% compared to the current design in the market. Carbon fibre was used as the material selected for the rigid frame. Through static simulation, the maximum stress value was 139.03 MPa was lower than the yield strength value which was 2263 MPa after a load of 2000N was applied. This represented a significant and effective improvements had been made through this research.